A governance model with an emphasis on the mediating role of social responsibility - Ghazal Rezaei Lori; Sanjar Salajegheh; Shiva Madahian; Amin Nikpour (Shahid Beheshti University of Medical Sciences, 2021)
Background: The purpose of the present study was to design a model of good governance to promote administrative health with an emphasis on the mediating role of social responsibility. Methods: The research method was descriptive and cross-sectional. The statistical population included a total number of 16504 employees working in Sirjan City. Based on the Morgan table, 377 employees were selected as the subjects of the study by using a convenience random sampling. Data collection was done through a researcher-developed questionnaire which was prepared based on the research literature. The 'Responsibility' variable was measured with 16 questions and the 'Good governance' variable was measured with 14 questions. Cronbach's alpha coefficient of variables was obtained higher than 0.7. To analyze the data, Confirmatory factor analysis and Structural equation modeling were used through Emus software. Results: According to the findings of factor analysis and fit indices, the indicators of the responsibility model are: intergenerational, environmental, and social commitments and the indicators of the good governance model are: sustainable governance and resource management. The direct effect between responsibility and good governance was obtained at 0.99. This study also showed a significant and direct relationship between the political, social, economic, and cultural dimensions of good governance and the interaction between industry and academia. Conclusion: Good governance as a fundamental variable and in interaction with other factors leads to the establishment of sustainable development in mines.